2008
DOI: 10.1590/2175-7860200859402
|View full text |Cite
|
Sign up to set email alerts
|

Chuva de sementes em uma área de vegetação de Caatinga no estado de Pernambuco

Abstract: RESUMO ABSTRACT(Seed rain in an area of Caatinga vegetation in Pernambuco State) The current study describes the composition and density of seed rain in one hectare of Caatinga vegetation. Forty seed traps of 0.25 m 2 each were set, and visited monthly during one year. Were sampled 76 seeds m 2 and 26 species. Tillandsia spp. (Bromeliaceae) contributed with the majority (49%) of seed deposition. There was no significative correlation between density of deposition of seeds and precipitation monthly. The seeds o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 27 publications
(16 reference statements)
1
4
0
9
Order By: Relevance
“…Moreover, the predominant dispersal syndrome in dry environments tends to vary with aridity and the predominance of life forms (herbs, vines, shrubs or trees). In some dry forests, dispersal by animals predominates (Griz & Machado 2001;Jara-Guerreiro et al 2011;Mart ınez-Garza et al 2011)' however, in other forests (primarily in semiarid environments), self-dispersal and wind dispersal predominate in both mature (Machado et al 1997;Ara ujo et al 2007;Lima et al 2008) and anthropogenic-disturbed forests (Teegalapalli et al 2010), as reported in our study. Nonetheless, despite the predominance of autochorous species in our study, species dispersed by animals were least represented in the young forest, indicating that dispersal by animals has not yet been completely re-established.…”
Section: Factors Limiting Seed Rain and Implications For Recolonisatisupporting
confidence: 72%
See 3 more Smart Citations
“…Moreover, the predominant dispersal syndrome in dry environments tends to vary with aridity and the predominance of life forms (herbs, vines, shrubs or trees). In some dry forests, dispersal by animals predominates (Griz & Machado 2001;Jara-Guerreiro et al 2011;Mart ınez-Garza et al 2011)' however, in other forests (primarily in semiarid environments), self-dispersal and wind dispersal predominate in both mature (Machado et al 1997;Ara ujo et al 2007;Lima et al 2008) and anthropogenic-disturbed forests (Teegalapalli et al 2010), as reported in our study. Nonetheless, despite the predominance of autochorous species in our study, species dispersed by animals were least represented in the young forest, indicating that dispersal by animals has not yet been completely re-established.…”
Section: Factors Limiting Seed Rain and Implications For Recolonisatisupporting
confidence: 72%
“…Most species absent from both forests were autochorous, possibly reflecting the predominance of Mimosaceae, Fabaceae, Caesalpiniaceae and Euphorbiaceae in the caatinga vegetation, most of which have autochorous dispersal (Lima et al . ; Souza ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Assim como algumas autocóricas possuem seus frutos dispersos secundariamente por animais, as anemocóricas possuem mecanismos diferenciados de dispersão. Um exemplo é em Herissantia crispa que, além de se dispersar sozinha, também foi considerada epizoocórica (Lima et al 2008, Judd et al 2009), pois seus propágulos são transportados no exterior do corpo de alguns animais, como aves e mamíferos. A dispersão pelo vento também pode ser facilitada por tufo de pelos nas sementes (Judd et al 2009), o que foi constatado em Calotropis procera.…”
Section: Resultsunclassified